2008
DOI: 10.1089/ten.tea.2007.0330
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cell Therapy for Intervertebral Disc Regeneration: AnIn VitroReconstructed Tissue in Alginate Capsules

Abstract: The degenerative pathologies of the intervertebral disc have a remarkable social impact in the industrialized countries and can provide serious disabilities in the population. The current treatment consists of conservative treatments (such as symptomatic pharmacological therapies and physiokinetic therapy) and surgical treatments (intervertebral fusion, total disc replacement, nucleus pulposus (NP) replacement, or surgical exeresis). Recent advances in cell therapy foresee the possibility of regenerating the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 59 publications
0
53
0
Order By: Relevance
“…Alginate is broadly used in in vitro experiments and provides an easy to control 3D cell culture environment. Previous studies have demonstrated differentiation of MSCs in alginate to NP-like cells [25,26] but direct comparison with medically approved, although for different applications, materials was not done before. Since a range of these medical devices are made of biological extracellular matrix molecules, we hypothesized that they may support equally to or better than alginate chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alginate is broadly used in in vitro experiments and provides an easy to control 3D cell culture environment. Previous studies have demonstrated differentiation of MSCs in alginate to NP-like cells [25,26] but direct comparison with medically approved, although for different applications, materials was not done before. Since a range of these medical devices are made of biological extracellular matrix molecules, we hypothesized that they may support equally to or better than alginate chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…To induce MSC chondrogenesis growth factors such as transforming growth factor (TGF)-b1, 2 or 3 [18], bone morphogenetic protein-2 [19], -4 [20], -7 [21] or -14 (GDF-5) [22], have been described to facilitate MSCs differentiation, however the aim of this project was to focus on the differences caused by variety of matrixes. In particular, many studies already described culture of MSCs embedded in several types of scaffolds, such as agarose gels [23], alginate beads [24][25][26], synthetic polymers [27,28] and other biomaterials [29][30][31][32]. These studies provide clear evidence that there is a need of a cell support for enhancing cell-cell and cell-matrix interactions and creating a 3D environment.…”
Section: Introductionmentioning
confidence: 99%
“…The degenerative pathologies of the intervertebral disc have a remarkable social impact in industrialized countries and can lead to serious disabilities (Gaetani et al, 2008;Ieda et al, 2010). Current treatment options consist of conservative treatments (such as symptomatic pharmacological therapies and physiokinetic therapy) and surgical treatments (intervertebral fusion, total disc replacement, nucleus pulposus replacement, or surgical exeresis) (Mauth et al, 2009;Wang and Campbell, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…ADSCs regenerative therapy has also been implied for the treatment of IVD diseases (O'Halloran and Pandit 2007;Gaetani et al 2008;Helder et al 2007;Li et al 2005;Richardson et al 2006): in fact, chondrocytes could be retrieved, expanded in a 3D in vitro system consisting of alginate capsules, and finally re-implanted through a mini-invasive technique. Moreover it is now possible to regenerate or replace damaged IVDs through the implants of biodegradable scaffolds seeded with autologous ADSCs previously induced to differentiate to the chondrogenic phenotype (Helder et al 2007).…”
Section: Adipose Stromal Vascular Fraction Encapsulation For Cartilagmentioning
confidence: 99%
“…Moreover, in rabbits, the adipose tissue-derived cells co-cultured with Nucleus Polposus (NP) cells showed a significant increase in the expression of type II collagen and aggrecan genes, suggesting that ADSCs might respond to mediators contained in the IVD (Li et al 2005). The barium alginate encapsulation technique applied by Gaetani et al (2008) showed that ADSCs improve the quality of in vitro reconstructed NP tissue for the regeneration of the human degenerated IVD. The results suggest that 3D coculture of NP cells and non-adipocyte cell fraction improves the quality of the in vitro reconstructed tissue in terms of the extracellular matrix production and cell organization.…”
Section: Adipose Stromal Vascular Fraction Encapsulation For Cartilagmentioning
confidence: 99%